Prevalência de alterações sensitivas e motoras em gestantes ambientalmente expostas ao mercúrio - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
Mercury exposure is a reality in the Amazon region, and its population is chronically exposed. Some population groups are considered at risk for this exposure, such as pregnant women, due to the possibility of transmission of mercury levels to the fetus. High levels of mercury exposure can cause damage to all body systems, especially the central nervous system, causing symptoms such as tremors, changes in motor coordination, muscle weakness, among others. Therefore, the objective of this study is to perform a sensory and motor assessment in pregnant women living in the urban area of Santarém who are exposed to mercury (Hg). The study was conducted in six Basic Health Units (UBS), where Hg levels were assessed through blood biomarkers, as well as a physical examination and application of tests to assess balance, sensitivity, motor coordination and cognitive tests. After analyzing the results, it was possible to observe that of the 63 pregnant women evaluated, 31.7% were considered to have high exposure, with Hg levels ranging from 0 to 24.95 μg/L; the average Hg level of the pregnant women was 3.24 μg/L (± 3.94), and the median was 1.68 μg/L. Among the pregnant women considered to have high exposure, only the sensitized Romberg tests, superficial and deep sensitivity, clinical tremor and Mini Mental State Examination (MMSE) were altered, and it was not possible to correlate them solely with mercury exposure, since it is necessary to consider the physiological and biomechanical factors of the gestational process. Therefore, it is possible to conclude that the gestational process, health history and other factors can also contribute to these alterations being identified in the physical examination. Longitudinal studies are needed to monitor the gestational process and fetal health conditions in order to prevent future complications, since the current study presents a cross-sectional portrait of the current gestational stage.
Keywords: Gestantes; Amazônia; Mercúrio; Intoxicação; Exposição Ambiental; CNPQ:: CIÊNCIAS DA SAÚDE